The Perceptions of Productive Asnaf Towards the Quality of Service and Assistance System by Baitul Mal Aceh, Indonesia - Nooramira Ghazali; Nur Izzati Ab Ghani; Hawa Husna Ab Ghani; Nadiah Rus Liyana Rusli (Human Resource Management Academic Research Society (HRMARS), 2023)
The effective implementation of modern and professional zakat management and service systems has opened a new chapter for various parties, especially zakat institutions. The quality of management and service is a crucial element in evaluating the ability of each zakat institution to achieve its goals. In Indonesia, Baitul Mal Aceh (BMA) excels due to its systematic management and service background. The institution has won several local awards for excellence in zakat management and administration. Hence, this study aims to assess how the productive asnaf group perceives the services and support provided by BMA, with the goal of evaluating the quality of assistance offered to this group. This study uses a qualitative research design through case studies and literature reviews. Primary data were obtained through unstructured interviews with 10 informants who received zakat assistance from BMA. Secondary data were obtained through scientific articles, books, journals, and official websites. The data obtained were analyzed through a thematic content analysis method. The result shows that productive asnaf have five positive perceptions towards the service and treatment provided by BMA. The implications of the study are also included in the discussion.